2019
DOI: 10.1016/j.knee.2019.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Short-term survival of cementless Oxford unicondylar knee arthroplasty based on the Finnish Arthroplasty Register

Abstract: Background: Cementless unicondylar knee arthroplasty (UKA) was introduced to secure longterm fixation and reduce the risk of revision. Experience with cementless UKA fixation is limited. Methods: The short-term survival (up to five years) of cementless Oxford UKA was assessed using data from the Finish Arthroplasty Register and was compared with that of cemented Oxford 3 UKA and total knee arthroplasty (TKA). Datawere obtained, from the Finnish Arthroplasty Register, on 1076 cementless Oxford UKAs and 2279 cem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 16 publications
(20 reference statements)
0
12
1
Order By: Relevance
“…In cementless OUKA, the most common reasons were osteoarthritis progression and infection. Our study's reoperation rate for bearing dislocation was higher than the rates from Western registry-based data (5,15). A meta-analysis by Ro,et al (16) found the mean reoperation rate per 100 observed component years for bearing dislocation after OUKA to be higher in Asians (0.53, 95% CI: 0.41-0.64) than in Westerners (0.14; 95% CI: 0.12-0.17).…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…In cementless OUKA, the most common reasons were osteoarthritis progression and infection. Our study's reoperation rate for bearing dislocation was higher than the rates from Western registry-based data (5,15). A meta-analysis by Ro,et al (16) found the mean reoperation rate per 100 observed component years for bearing dislocation after OUKA to be higher in Asians (0.53, 95% CI: 0.41-0.64) than in Westerners (0.14; 95% CI: 0.12-0.17).…”
Section: Discussioncontrasting
confidence: 68%
“…However, contradictory results were reported from larger or longer-term studies. Knifsund, et al (15) collected data from the Finnish Arthroplasty Register, and they found the 5-year survival of cemented OUKA to be signi cantly shorter than that of cementless OUKA (88.9% vs. 92.3%, p<0.05). A large propensity-matched NJR-based study also showed the risk of revision in cementless OUKA to be 24% less than that of cemented OUKA within 10 years (5).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the inferior survival of unicompartmental arthroplasty in registries, many orthopaedic surgeons and patients believe in the potential superior functional outcome of medial unicompartmental arthroplasty compared with total knee arthroplasty. 12 13 30 31 Given these expectations, a assessor-blind setup is the most reliable method for comparing these devices. Another strength of our study was that it was conducted in the public sector in publicly funded hospitals and the authors did not receive any grants or other funding from industry.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…[8][9][10][11] Although several studies have reported good long-term results in single-centre series for medial unicompartmental knee arthroplasty, its survival has been inferior to that of total knee arthroplasty in national registries. 12 13 Therefore, whether patients should undergo unicompartmental or total knee arthroplasties at all is open to debate.…”
Section: Introductionmentioning
confidence: 99%
“…Unicompartmental knee arthroplasty (UKA) is a well-established treatment for patients with isolated compartmental knee arthritis. Advantages of UKA over total knee arthroplasty (TKA) include reduced morbidity and mortality, preservation of normal knee kinematics and faster recovery [ 35 , 49 , 59 ]. However, national registry data have shown lower revision rates after TKA in comparison to UKA [ 49 , 66 ].…”
Section: Introductionmentioning
confidence: 99%